Opportunities and criticisms of voluntary emission reduction projects developed by Public Administrations: Analysis of 143 case studies implemented in Italy. (1st October 2016) - Gallo, Michela; Del Borghi, Adriana; Strazza, Carlo; Parodi, Lara; Arcioni, Livia; Proietti, Stefania
Highlights: 143 voluntary emission reduction projects have been analysed. The projects belong to renewable energy, energy efficiency and transport sectors. Voluntary emission reduction standards and methodologies have been applied. The paper identified the main criticisms for each sector. Energy efficiency projects are the most promising for public entities. Abstract: The United Nations Framework Convention on Climate Change (UNFCCC) sets an overall framework for intergovernmental efforts to tackle the challenge posed by climate change. Besides the "flexibility mechanisms" defined by the Kyoto Protocol to lower the overall costs of achieving their emissions targets, The Voluntary Green House Gases (GHG) reduction projects can have a lead role in GHG reduction in "non Emissions Trading System ETS sectors". Nowadays, the voluntary market is characterised by critical aspects, such as fragmentation, lack of accounting, monitoring and validation rules that have led to the low spread of voluntary emission reduction projects developed by local authorities in the European Union despite their high potentiality. The aim of this paper is to test the applicability of voluntary emission reduction projects in the public sector following a homogeneous and consistent pattern. A research has been performed at local level on 143 voluntary emission reduction projects implemented by Public Administrations in Northern and Central Italy in renewable energy, energy efficiency and transport sectors. The applicable standards and methodologies have been checked and the case studies have been analysed though a three-step process: Preliminary additionality assessment; Projects selection; Validation of the selected project. The assessment shows that energy efficiency projects, once overcoming additionality issues, are the most promising for public entities while renewable energy and transport projects resulted to be mainly affected by double counting problems and lack of reliable methodologies.